THE IMPACT OF GIANYAR TRADITIONAL MARKET REVITALIZATION ON THE INCOME OF VEGETABLE AND FRUIT TRADERS - Arintus Hatu; Ida Ayu Made Dwi Susanti; I Made Tamba (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2026)
The revitalization of traditional markets is a strategic effort by the government to enhance competitiveness, particularly in response to declining infrastructure quality and reduced consumer interest. This study is motivated by the condition of the Gianyar People’s Market, which was considered inadequate, prompting a revitalization program aimed at improving traders’ welfare. The objective of this research is to analyze the impact of market revitalization on the income of vegetable and fruit traders. The study was conducted at the Gianyar People’s Market, Gianyar Regency. A mixed-method approach was employed, combining quantitative and qualitative data derived from primary and secondary sources. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out using income analysis, descriptive analysis, and the McNemar test to examine differences in traders’ income before and after revitalization. The results indicate that the implementation of the revitalization program led to a significant decrease in the income of vegetable and fruit traders. This decline was primarily attributed to a reduction in the number of visitors, suboptimal market management, and ineffective governance by the local authorities. Statistical analysis further confirms that market revitalization has a significant effect on traders’ income. In conclusion, the revitalization of the Gianyar People’s Market has not yet achieved its intended objective of improving traders’ income. Therefore, improvements in market management and governance are necessary to ensure the effectiveness of future revitalization programs